Introduction: An ICMI Study on Language Diversity in Mathematics Education - Barwell, Richard; Clarkson, Philip; Halai, Anjum; Kazima, Mercy; Moschkovich, Judit; Planas, Núria; Phakeng, Mamokgethi; Valero, Paola; Ubillús, Martha (2016)
This chapter provides the introduction to this ICMI Study 21 volume. It includes: a discussion of the place of this study and its topic within ICME; a discussion of what is meant by the study title; and a brief historical account of research on this topic in mathematics education. The chapter also recounts the various stages of the study, including the development of the discussion document, the study conference, and the preparation of this volume. The latter parts of the chapter include syntheses of some key research ideas emerging from the volume, implications for policy and practice and issues for further research. © The Editor(s) and the Author(s) 2015, corrected publication 2021 Open Access This book was originally published with exclusive rights reserved by the Publisher in 2015 and was licensed as an open access publication in March 2021 under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (http://creativecommons.org/licenses/ by-nc-nd/4.0/), which permits any noncommercial use, sharing, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence and indicate if you modified the licensed material. You do not have permission under this licence to share adapted material derived from this book or parts of it. The book homepage is: https://link.springer.com/book/10.1007%2F978-3-319-14511-2#about
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-319-14511-2_1 4752638:3YQI776Q
Keywords: _C:Malawi MWI